2014
DOI: 10.1136/bjsports-2014-093624
|View full text |Cite
|
Sign up to set email alerts
|

Is iron treatment beneficial in, iron-deficient but non-anaemic (IDNA) endurance athletes? A systematic review and meta-analysis

Abstract: These results indicate iron treatments improve the iron status and aerobic capacity of iron deficient non-anaemic endurance athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 63 publications
1
91
2
2
Order By: Relevance
“…Other studies claim that ID can induce muscle and hormonal dysfunction and predispose to infection [27]. Recently, Burden et al [28] found that iron supplementation has a positive effect on aerobic capacity (VO 2 max) . In other studies, iron-supplemented subjects without anemia showed improved performance and/or VO 2 max [12].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies claim that ID can induce muscle and hormonal dysfunction and predispose to infection [27]. Recently, Burden et al [28] found that iron supplementation has a positive effect on aerobic capacity (VO 2 max) . In other studies, iron-supplemented subjects without anemia showed improved performance and/or VO 2 max [12].…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency anaemia is caused by insufficient consumption of iron (or insufficient absorption of iron) and is a decrease in red blood cells (RBCs) or haemoglobin, leading to symptoms such as tiredness and fatigue; weakness, shortness of breath and reduced exercise tolerance (Longo and Camaschella, 2015). Iron deficiency without anaemia has also been shown to reduce endurance capacity, increase energy expenditure and impair adaptation to endurance exercise in females experiencing tissue depletion (Burden et al, 2015).Calcium also have significant effect on growth and development insufficient dietary calcium have negative impact on health and increase the risk of diseases such as osteoporosis (Kin et al, 2007;Morris et al, 2008). Zinc acts as a cofactor of various enzymes involved in macronutrient metabolism and cell replication (Soetan et al, 2010;Arinola, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to describe this issue and to understand its implications. Interventions to support female athletes such as iron therapy,6 and an increased awareness of HMB among sports medicine professionals could have far reaching benefits for the female athlete.…”
mentioning
confidence: 99%